The politics of waste in later medieval England, c.1270-1490 - Peake, Joseph (2024)
The politics of waste in later medieval England, c. 1270-1490 investigates the concept of waste in relation to the politics and culture of England from around the start of the reign of Edward I until the very early years of the Tudor era. Drawing from a variety of sources including petitions, chancery records, manor court rolls, political and legal treatises, legislation, chronicles, and verse romances, it shows how the concept of waste was intertwined with institutional standards of equity, justice and property-holding. Whereas waste has generally been associated with a lack or loss of material value by historians of this period, this thesis argues instead that the concept was useful as a tool of political rhetoric at multiple levels of society, on account of the benefits and detriments that cases of waste could bring to different parties in the same instance. Waste lands could be seen as sought-after sites of potential settlement or resource extraction, as both manorial records and chronicles show, and yet they could also be seen as the consequence of the decline or devastation of a settled area. Similarly, to devastate a land or ‘make waste’ with regard to another’s property could often be profitable to those carrying it out, be it the recycling of a disused seigneurial tenement or the goods seized by an army from enemy territories. Waste could at times be legitimised, such as in the destruction and resource-stripping of the property of enemies and felons at the behest of the Crown, and cases where this legitimacy was challenged or questioned show how understandings of waste were constantly subject to negotiation. Waste was, therefore, a highly contested concept, with different actors at various points trying to define and deploy it to suit their own agendas.